Molecular analysis of oral microflora in patients with primary Sjögren’s syndrome by using high-throughput sequencing - Zhifang Zhou; Guanghui Ling; Ning Ding; Zhe Xun; Ce Zhu; Hong Hua; Xiaochi Chen (PeerJ, 2018)
Background The objective of this study was to characterize the oral microflora profile of primary Sjögren’s syndrome (pSS) patients, thereby revealing the connection between oral bacterial composition and dental caries, and to identify the “core microbiome” in the oral cavities of pSS patients and systemic healthy individuals by using a high-throughput sequencing technique. Methods Twenty-two pSS patients and 23 healthy controls were enrolled in this study. Their clinical data and oral rinse samples were collected. The V3–V4 hypervariable regions of the bacterial 16S rRNA gene of samples were amplified and analyzed by high-throughput sequencing on the Illumina Miseq PE300 platform. Results Both two groups were age- and sex-matched. There were significantly higher decayed, missing and filled teeth (DMFT) and decayed, missing and filled surfaces (DMFS) in the pSS group than in the control group (p < 0.01). Alpha diversity was depleted in pSS patients, compared with healthy controls (p < 0.01), while beta diversity between the two groups was not significantly different. Seven discriminative genera (LDA > 4) were found between the two groups in LEfSe (LDA Effect Size) analysis. The relative abundance of Veillonella in pSS patients was fourfold higher, while Actinomyces, Haemophilus, Neisseria, Rothia, Porphyromonas and Peptostreptococcus were significantly lower in pSS patients than in healthy controls. However, the correlation between Veillonella and DMFT/DMFS was not significant (p > 0.05). In Venn diagram analysis, nine genera shared by all samples of two groups, which comprised 71.88% and 67.64% in pSS patients and controls, respectively. Discussion These findings indicate a microbial dysbiosis in pSS patients; notably, Veillonella might be recognized as a biomarker in pSS patients. The core microbiome in pSS patients was similar to the systemic healthy population. These provide insight regarding advanced microbial prevention and treatment of severe dental caries in pSS patients. This study also provides basic data regarding microbiology in pSS.